2010
DOI: 10.1262/jrd.09-107h
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol-supplemented Calcium-free Media Improve Zona Penetration of Vitrified Rat Oocytes by Sperm Cells

Abstract: Abstract. Cryopreservation of matured oocytes is a useful technique because the oocytes can be used for some assisted reproductive technologies after warming. Even though rats, like mice, have been used in various research fields including reproductive technology, information about cryopreservation of rat oocytes is limited. The objective of the present study was to improve the vitrification protocol for matured rat oocytes. To determine the optimal equilibration time, oocytes were equilibrated in 7.5% ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…In that case, performing vitrification in calcium-free medium reduced zona pellucida hardening and enhanced the fertilization rate and development [7,17]. In the present study, we produced vitrified eggs using EG only or EG+ DMSO, which recovered from cryodamage after a period of incubation and then, we investigated the changes of longlasting [Ca 2+ ] i oscillation [30].…”
Section: Discussionmentioning
confidence: 91%
“…In that case, performing vitrification in calcium-free medium reduced zona pellucida hardening and enhanced the fertilization rate and development [7,17]. In the present study, we produced vitrified eggs using EG only or EG+ DMSO, which recovered from cryodamage after a period of incubation and then, we investigated the changes of longlasting [Ca 2+ ] i oscillation [30].…”
Section: Discussionmentioning
confidence: 91%
“…Its effect seems to be beyond being a permeable CP because some interaction between EG and calcium seems to take place. When rat oocytes were vitrified in vitrification solution of 15% EG, 15% DMSO, and 0.5 M sucrose and 20% FCS, survival and cleavage rate after activation of vitrified warmed oocytes was 98.3 and 78.4% respectively, but zona pellucida sperm penetration rate was very low (3.6%, 6/168) and a high level of cortical granule exocytosis was noted (Fujiwara et al 2010). When the oocytes were vitrified in EG-supplemented calcium-free media without DMSO, they had 79.4% survival, 72.8% cleavage after activation, 63.9% zona pellucida penetration, and 23.1% of the oocytes developed to blastocyst.…”
Section: Eg and Calciummentioning
confidence: 99%
“…The females were superovulated by intraperitoneal injections of equine chorionic gonadotropin (eCG: PMS‐A 1000 for animals, Nippon Zenyaku Kogyo Co., Ltd., Fukushima, Japan) 300 IU/kg of body weight and of human chorionic gonadotropin (hCG: Gonatropin, ASKA Pharmaceutical Co., Ltd. Tokyo, Japan) 300 IU/kg of body weight at 48 h intervals, as previously reported by Fujiwara et al . (). During the first 12 to 14 h after the hCG injection, oocytes composed of masses of surrounding cumulus cells were collected from the oviductal ampullae of the donor females with modified Dulbecco's phosphate buffered medium (PB1: Whittingham & Wales ) calcium free supplemented with 1% (v/v) fetal calf serum (FCS: Life Technologies, Carlsbad, CA, USA), and then COCs were individually separated from the mass of cumulus‐matrix including several COCs by pipetting.…”
Section: Methodsmentioning
confidence: 97%
“…Although matured rat oocytes vitrified with ethylene glycol (EG) survived after warming, the oocytes were not fertilized after IVF with fresh sperm (Fujiwara et al . ). In that study, sperm have been observed in the perivitelline space of the vitrified/warmed oocytes after IVF.…”
Section: Introductionmentioning
confidence: 97%